"It's Not about the Money. It's about Sending a Message!" Unpacking the Components of Revenge - Andras Molnar; Shereen J. Chaudhry; George Loewenstein (Center for Economic Studies and ifo Institute (CESifo), 2020)
We examine whether belief-based preferences - caring about what transgressors believe - play a crucial role in punishment decisions: Do punishers want to make sure that transgressors understand why they are being punished, and is this desire to affect beliefs often prioritized over distributive and retributive preferences? We test whether punishers derive utility from three distinct sources: material outcomes (their own and the transgressor's payoff), affective states (the transgressor's suffering), and cognitive states (the transgressor's beliefs about the cause of that suffering). In a novel, preregistered experiment (N = 1,959) we demonstrate that consideration for transgressors' beliefs affects punishment decisions on its own, regardless of the considerations for material outcomes (distributional preferences) and affective states (retributive preferences). By contrast, we find very little evidence for pure retributive preferences (i.e., to merely inflict suffering on transgressors). We also show that people who would otherwise enact harsh punishments, are willing to punish less severely, if by doing so they can tell the transgressor why they are punishing them. Finally, we demonstrate that the preference for affecting transgressors' beliefs cannot be explained by deterrence motives (i.e., to make transgressors behave better in the future).
Keywords: C91; D63; D82; D83; 330; beliefs; belief-based utility; justice; fairness; morality; punishment; revenge